Piezoelectric thin film, piezoelectric thin film element, and piezoelectric transducer

JP2025020943APending Publication Date: 2025-02-13TDK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023124586
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0023】 本発明の一側面によれば、圧電特性に優れた圧電薄膜、当該圧電薄膜を含む圧電薄膜素子、及び圧電薄膜又は圧電薄膜素子を含む圧電トランスデューサが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020943000001_ABST
    Figure 2025020943000001_ABST
Patent Text Reader

Abstract

To provide a piezoelectric thin film with excellent piezoelectric properties.SOLUTION: A piezoelectric thin film 3 includes a metal oxide having a perovskite structure. The metal oxide includes bismuth, potassium, titanium, magnesium, iron, and an element M. The element M is at least one element selected from the group consisting of gallium and cobalt. At least a part of the metal oxide is at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals. The (001) plane of the crystal is oriented in a normal direction dn of the surface of the piezoelectric thin film 3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a piezoelectric thin film, a piezoelectric thin film element, and a piezoelectric transducer. [Background technology]

[0002] Piezoelectric bodies are processed into various piezoelectric elements for various purposes. For example, a piezoelectric actuator converts voltage into force by applying a voltage to a piezoelectric body to deform the piezoelectric body through the inverse piezoelectric effect. For example, a piezoelectric sensor converts force into voltage by applying pressure to a piezoelectric body to deform the piezoelectric body through the piezoelectric effect. These piezoelectric elements are mounted in various electronic devices. In recent years, the market has been demanding miniaturization and improved performance of electronic devices, so piezoelectric elements (piezoelectric thin film elements) using piezoelectric thin films have been actively researched. However, the thinner the piezoelectric body, the more difficult it is to obtain the piezoelectric effect and inverse piezoelectric effect, so there is a demand for the development of piezoelectric bodies that have excellent piezoelectric properties in a thin film state.

[0003] Conventionally, lead zirconate titanate (PZT), a perovskite-type ferroelectric, has been widely used as a piezoelectric material. However, since PZT contains lead, which is harmful to the human body and the environment, the development of lead-free piezoelectric materials as an alternative to PZT is expected. For example, the following Non-Patent Document 1 describes BaTiO3-based materials as an example of lead-free piezoelectric materials. BaTiO3-based materials have relatively excellent piezoelectric properties among lead-free piezoelectric materials, and are particularly expected to be applied to piezoelectric thin film elements. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Yiping GUO et al., “ThicknessDependence of Electrical Properties of Highly (100)-Oriented BaTiO3Thin Films Prepared by One-Step Chemical Solution Deposition” Japanese Journal of Applied Physics, Vol.45, No.2A, 2006, pp.855-859 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of one aspect of the present invention is to provide a piezoelectric thin film having excellent piezoelectric characteristics, a piezoelectric thin film element including the piezoelectric thin film, and a piezoelectric transducer including the piezoelectric thin film or the piezoelectric thin film element. [Means for solving the problem]

[0006] For example, one aspect of the present invention relates to a piezoelectric thin film described in any one of the following [1] to [5], a piezoelectric thin film element described in any one of the following [6] to

[14] , and a piezoelectric transducer described in any one of the following

[15] and

[16] .

[0007] [1] A piezoelectric thin film comprising a metal oxide having a perovskite structure, the metal oxide comprises bismuth, potassium, titanium, magnesium, iron, and the element M; The element M is at least one element selected from the group consisting of gallium and cobalt; At least a part of the metal oxide is at least one crystal selected from the group consisting of tetragonal crystal and orthorhombic crystal; The (001) plane of the crystal is oriented in the normal direction to the surface of the piezoelectric thin film. Piezoelectric thin film.

[0008] [2] The metal oxide is represented by the following chemical formula 1: In the following chemical formula 1, x, y, and z are each a positive real number, x+y+z is 1, In the following chemical formula 1, α is greater than 0 and less than 1, In the following chemical formula 1, β is greater than 0 and less than 1, In the following chemical formula 1, γ is 0.05 or more and 0.40 or less, In the following chemical formula 1, M is Ga 1-δ Co δ It is expressed as δ is between 0 and 1, [1] The piezoelectric thin film according to claim 1. x(Bi 1-α K α )TiO3‐yBi(Ti 1-β Mg β )O3‐zBi(Fe 1-γ M γ )O3(1)

[0009] [3] A three-dimensional coordinate system is made up of X, Y, and Z axes. Any coordinate in the coordinate system is expressed as (X,Y,Z), Coordinates (x, y, z) in the coordinate system represent x, y, and z in Chemical Formula 1; The coordinate A in the coordinate system is (0.250, 0.005, 0.700), The coordinate B in the coordinate system is (0.450, 0.250, 0.300), The coordinate C in the coordinate system is (0.200, 0.500, 0.300), The coordinate D in the coordinate system is (0.005, 0.250, 0.700), The coordinates (x,y,z) lie within a rectangle whose vertices are coordinates A, B, C, and D. [2] The piezoelectric thin film according to claim 1.

[0010] [4] It is an epitaxial film. The piezoelectric thin film according to any one of [1] to [3].

[0011] [5] Ferroelectric thin films: The piezoelectric thin film according to any one of [1] to [4].

[0012] [6] A piezoelectric thin film comprising the piezoelectric thin film according to any one of [1] to [5]. Piezoelectric thin film element.

[0013] [7] A crystalline substrate; a piezoelectric thin film directly or indirectly overlying a crystalline substrate; Including, The piezoelectric thin film element according to [6].

[0014] [8] A crystalline substrate; an electrode layer directly or indirectly overlying the crystalline substrate; a piezoelectric thin film directly or indirectly overlapping the electrode layer; Including, The piezoelectric thin film element according to [6].

[0015] [9] an electrode layer; a piezoelectric thin film directly or indirectly overlapping the electrode layer; Including, The piezoelectric thin film element according to [6].

[0016]

[10] Further comprising at least one intermediate layer (first intermediate layer), an intermediate layer (first intermediate layer) is disposed between the crystalline substrate and the electrode layer; The piezoelectric thin film element according to [8].

[0017]

[11] Further comprising at least one intermediate layer (second intermediate layer), an intermediate layer (second intermediate layer) is disposed between the electrode layer and the piezoelectric thin film; The piezoelectric thin film element according to [8].

[0018]

[12] Further comprising at least one intermediate layer (second intermediate layer), an intermediate layer (second intermediate layer) is disposed between the electrode layer and the piezoelectric thin film; [9] The piezoelectric thin film element according to [9].

[0019]

[13] The electrode layer includes platinum crystals; The (002) plane of the platinum crystal is oriented in the normal direction to the surface of the electrode layer, The (200) plane of the platinum crystal is oriented in the in-plane direction of the surface of the electrode layer. The piezoelectric thin film element according to [8] or

[11] .

[0020]

[14] The electrode layer includes platinum crystals; The (002) plane of the platinum crystal is oriented in the normal direction to the surface of the electrode layer, The (200) plane of the platinum crystal is oriented in the in-plane direction of the surface of the electrode layer. The piezoelectric thin film element according to [9] or

[12] .

[0021]

[15] A piezoelectric thin film comprising the piezoelectric thin film according to any one of [1] to [5]. Piezoelectric transducer.

[0022]

[16] A piezoelectric thin film element comprising the piezoelectric thin film element according to any one of [6] to

[14] . Piezoelectric transducer. Effect of the Invention

[0023] According to one aspect of the present invention, there are provided a piezoelectric thin film having excellent piezoelectric characteristics, a piezoelectric thin film element including the piezoelectric thin film, and a piezoelectric transducer including the piezoelectric thin film or the piezoelectric thin film element. [Brief description of the drawings]

[0024] [Figure 1] (a) in Figure 1 is a schematic cross-sectional view of a piezoelectric thin film element according to one embodiment of the present invention, and (b) in Figure 1 is an oblique exploded view of the piezoelectric thin film element shown in (a) in Figure 1, with the substrate, first intermediate layer, second intermediate layer and second electrode layer omitted in (b) in Figure 1. [Diagram 2] FIG. 2 is a perspective view of a crystal (unit cell) of a metal oxide having a perovskite structure, and shows the arrangement of each element in the perovskite structure. [Diagram 3] FIG. 3 is a perspective view of a crystal (unit cell) of a metal oxide having a perovskite structure, showing the lattice planes and crystal orientation of the crystal. [Figure 4] FIG. 4 is a three-dimensional coordinate system for showing the composition of the piezoelectric thin film. [Diagram 5] FIG. 5 is a triangular coordinate system corresponding to the triangle shown in FIG. [Figure 6] FIG. 6 is a schematic cross-sectional view of a piezoelectric thin film element (ultrasonic transducer) according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] A preferred embodiment of the present invention will be described in detail below with reference to the drawings. However, the present invention is not limited to the following embodiment. In the drawings, the same or equivalent elements are given the same reference numerals. The X-axis, Y-axis, and Z-axis shown in FIG. 1(a), FIG. 1(b), and FIG. 6 are three coordinate axes that are orthogonal to each other. The X-axis, Y-axis, and Z-axis are common to FIG. 1(a), FIG. 1(b), and FIG. 6, but the coordinate system shown in FIG. 1(a), FIG. 1(b), and FIG. 6 is not related to the coordinate system shown in FIG. 4 and FIG. 5.

[0026] (Piezoelectric thin film element) The piezoelectric thin film element according to this embodiment includes at least a piezoelectric thin film. For example, as shown in (a) of FIG. 1, the piezoelectric thin film element 10 according to this embodiment may include a crystalline substrate 1, a first electrode layer 2 (lower electrode layer) directly or indirectly overlapping the crystalline substrate 1, a piezoelectric thin film 3 directly or indirectly overlapping the first electrode layer 2, and a second electrode layer 4 (upper electrode layer) directly or indirectly overlapping the piezoelectric thin film 3. The piezoelectric thin film element 10 may further include at least one intermediate layer. For example, the piezoelectric thin film element 10 may include a first intermediate layer 5. The first intermediate layer 5 may be disposed between the crystalline substrate 1 and the first electrode layer 2, and the first electrode layer 2 may be directly overlapping the surface of the first intermediate layer 5. The piezoelectric thin film element 10 may include a second intermediate layer 6. The second intermediate layer 6 may be disposed between the first electrode layer 2 and the piezoelectric thin film 3, and the piezoelectric thin film 3 may be directly overlapping the surface of the second intermediate layer 6. The thicknesses of the crystalline substrate 1, the first intermediate layer 5, the first electrode layer 2, the second intermediate layer 6, the piezoelectric thin film 3, and the second electrode layer 4 may be uniform. As shown in FIG. 1B, the normal direction dn of the surface of the piezoelectric thin film 3 is perpendicular to the normal direction D N The normal direction dn to the surface of the piezoelectric thin film 3 is the polarization direction of the piezoelectric thin film 3. The normal direction dn to the surface of the piezoelectric thin film 3 may be rephrased as the thickness direction of the piezoelectric thin film 3.

[0027] A modified example of the piezoelectric thin film element 10 may not include the crystalline substrate 1. For example, the crystalline substrate 1 may be removed after the first electrode layer 2, the piezoelectric thin film 3, and the second electrode layer 4 are formed. When the crystalline substrate 1 functions as an electrode, the crystalline substrate 1 may be the first electrode layer 2. That is, when the crystalline substrate 1 functions as an electrode, a modified example of the piezoelectric thin film element 10 may include the crystalline substrate 1 and the piezoelectric thin film 3 overlapping the crystalline substrate 1. When the crystalline substrate 1 functions as an electrode, the piezoelectric thin film 3 may directly overlap the crystalline substrate 1. When the crystalline substrate 1 functions as an electrode, the piezoelectric thin film 3 may overlap the crystalline substrate 1 via at least one intermediate layer selected from the first intermediate layer 5 and the second intermediate layer 6.

[0028] The piezoelectric thin film 3 contains a metal oxide having a perovskite structure. The metal oxide contains bismuth (Bi), potassium (K), titanium (Ti), magnesium (Mg), iron (Fe), and element M. The element M is at least one element selected from the group consisting of gallium (Ga) and cobalt (Co). A metal oxide having the above composition is likely to become at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals, and the (001) plane of the crystal is likely to be oriented in the normal direction to the surface of the piezoelectric thin film. As a result, the piezoelectric thin film 3 has excellent piezoelectric characteristics (large piezoelectric strain constant d 33,f ) and can have ferroelectric properties. The metal oxide may consist only of Bi, K, Ti, Mg, Fe, element M, and oxygen (O). The metal oxide may contain other elements in addition to Bi, K, Ti, Mg, Fe, element M, and O. The metal oxide may further contain at least one element selected from the group consisting of lanthanum (La), yttrium (Y), sodium (Na), lithium (Li), zirconium (Zr), nickel (Ni), zinc (Zn), manganese (Mn), and lead (Pb). However, the metal oxide does not have to contain Pb. The metal oxide is the main component of the piezoelectric thin film 3. The ratio of all elements constituting the metal oxide in the piezoelectric thin film 3 may be 99 mol% or more and 100 mol% or less. The piezoelectric thin film 3 may be composed only of the metal oxide. The piezoelectric thin film 3 may contain other elements in addition to Bi, K, Ti, Mg, Fe, element M, and O, so long as the piezoelectric characteristics of the piezoelectric thin film 3 are not impaired. For example, the piezoelectric thin film 3 may further contain at least one element selected from the group consisting of La, Y, Na, Li, Zr, Ni, Zn, Mn, and Pb. However, the piezoelectric thin film 3 does not have to contain Pb.

[0029] Hereinafter, the above metal oxide having a perovskite structure is referred to as a "perovskite oxide". FIG. 2 shows a unit cell of a crystal of a perovskite oxide. The element located at the A site of the unit cell uc is Bi or K. The element located at the B site of the unit cell uc is Ti, Mg, Fe, or element M. The unit cell uc shown in FIG. 2 is the same as the unit cell uc shown in FIG. 3. However, in FIG. 3, the B site and oxygen (O) in the unit cell uc are omitted in order to show the lattice plane. The lattice translation vector a (i.e., a-axis) in the unit cell uc is oriented in the

[0100] direction, the lattice translation vector b (i.e., b-axis) in the unit cell uc is oriented in the

[0010] direction, and the lattice translation vector c (i.e., c-axis) in the unit cell uc is oriented in the

[0001] direction. The lattice translation vector a, the lattice translation vector b, and the lattice translation vector c are perpendicular to each other. The length a of the lattice translation vector a is the spacing a of the (100) planes of the perovskite oxide (lattice constant a). The length b of the lattice translation vector b is the spacing b of the (010) planes of the perovskite oxide (lattice constant b). The length c of the lattice translation vector c is the spacing c of the (001) planes of the perovskite oxide (lattice constant c). The piezoelectric thin film 3 may be made of a single crystal of a perovskite oxide. The piezoelectric thin film 3 may be made of a polycrystal of a perovskite oxide.

[0030] At room temperature or at a temperature equal to or lower than the Curie temperature of the perovskite oxide, a part or all of the perovskite oxide is at least one crystal selected from the group consisting of tetragonal crystal and orthorhombic crystal. Due to the anisotropy in the c-axis of either the tetragonal crystal or the orthorhombic crystal, the piezoelectric thin film 3 can have excellent piezoelectric properties and ferroelectricity. In the tetragonal crystal, the lattice constant a is equal to the lattice constant b. In the tetragonal crystal, the lattice constant a is different from the lattice constant c. In the tetragonal crystal, the lattice constant c may be larger than the lattice constant a. In the orthorhombic crystal, the lattice constant a, the lattice constant b, and the lattice constant c are different from each other. In the orthorhombic crystal, the lattice constant c may be larger than each of the lattice constant a and the lattice constant b. The perovskite oxide may be composed of only the tetragonal crystal. The perovskite oxide may be composed of only the orthorhombic crystal. The perovskite oxide may be composed of only tetragonal and orthorhombic crystals. The piezoelectric thin film 3 may further include crystals other than tetragonal and orthorhombic crystals. For example, the piezoelectric thin film 3 may further include one or both of cubic crystals of the perovskite oxide and rhombohedral crystals of the perovskite oxide.

[0031] The (001) plane of at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals is oriented in the normal direction dn of the surface of the piezoelectric thin film 3. The piezoelectric thin film 3 may include a plurality of crystals, and the (001) planes of some or all of the crystals in the piezoelectric thin film 3 may be oriented in the normal direction dn of the surface of the piezoelectric thin film 3. For example, the (001) plane of the crystal (unit cell uc) may be approximately or completely perpendicular to the normal direction dn, and the

[0001] (lattice plane orientation) of the crystal (unit cell uc) may be approximately or completely parallel to the normal direction dn. In other words, the (001) plane of the crystal (unit cell uc) may be approximately or completely parallel to the surface of the piezoelectric thin film 3. The crystal orientation in which the perovskite oxide having the above-mentioned composition is easily polarized is

[0001] . Therefore, the (001) plane of the crystal of the perovskite oxide is oriented in the normal direction dn of the surface of the piezoelectric thin film 3, so that the piezoelectric thin film 3 can have excellent piezoelectric properties and ferroelectricity. For the same reason, for example, c / a of each of the tetragonal crystal and the orthorhombic crystal may be 1.05 or more and 1.20 or less. For example, the lattice constant a of each of the tetragonal crystal and the orthorhombic crystal may be 0.375 Å or more and 0.395 Å or less. The lattice constant b of the tetragonal crystal is equal to the lattice constant a of the tetragonal crystal. For example, the lattice constant b of the orthorhombic crystal may be 0.375 Å or more and 0.395 Å or less, and may be a value different from the lattice constant a of the orthorhombic crystal. For example, the lattice constant c of each of the tetragonal crystal and the orthorhombic crystal may be 0.430 Å or more and 0.450 Å or less. The c / a of the tetragonal crystal may be the same as or different from the c / a of the orthorhombic crystal. The lattice constant a of the tetragonal crystal may be the same as or different from the lattice constant a of the orthorhombic crystal. The lattice constant c of the tetragonal crystal may be the same as or different from the lattice constant c of the orthorhombic crystal.

[0032] The degree of orientation of each lattice plane of the crystal may be quantified by the degree of orientation (unit: %). The degree of orientation of each lattice plane may be calculated based on the peak of the diffracted X-ray originating from each lattice plane. The peak of the diffracted X-ray originating from each lattice plane may be measured by out of plane measurement on the surface of the piezoelectric thin film 3. The degree of orientation of the (001) plane is 100×I (001) / ΣI (hkl) The orientation of the (110) plane can be expressed as 100×I(110) / ΣI (hkl) The orientation of the (111) plane is 100×I (111) / ΣI (hkl) It may be expressed as: I (001) is the maximum value of the diffracted X-ray peak originating from the (001) plane. I (110) is the maximum value of the diffracted X-ray peak originating from the (110) plane. (111) is the maximum peak of the diffracted X-rays originating from the (111) plane. ΣI (hkl) I (001) +I (110) +I (111) The orientation of the (001) plane is 100×S (001) / ΣS (hkl) The orientation of the (110) plane can be expressed as 100×S (110) / ΣS (hkl) The orientation of the (111) plane can be expressed as 100×S (111) / ΣS (hkl) It may be expressed as: S (001) is the area of ​​the diffracted X-ray peak (peak integral) originating from the (001) plane. S (110) is the area of ​​the diffracted X-ray peak (peak integral) originating from the (110) plane. S (111) is the area of ​​the diffracted X-ray peak (peak integral) originating from the (111) plane. ΣS (hkl) is S (001) +S (110) +S (111) The degree of orientation of each lattice plane may be quantified by the degree of orientation based on the Lotgering method.

[0033] It is preferable that the (001) plane of the crystal is preferentially oriented in the normal direction dn of the surface of the piezoelectric thin film 3, because this tends to give the piezoelectric thin film 3 excellent piezoelectric properties and ferroelectricity. In other words, it is preferable that the degree of orientation of the (001) plane is higher than the degrees of orientation of each of the (110) plane and the (111) plane. For example, the degree of orientation of the (001) plane may be 70% or more and 100% or less, preferably 80% or more and 100% or less, and more preferably 90% or more and 100% or less.

[0034] In contrast to the piezoelectric thin film 3, it is difficult to distort the bulk of a piezoelectric body having a cubic crystal structure or a pseudo cubic crystal structure to make the bulk of the piezoelectric body into a tetragonal or orthorhombic crystal, and therefore the bulk of the piezoelectric body tends not to have the piezoelectric properties resulting from the tetragonal or orthorhombic crystal structure of a perovskite oxide.

[0035] The crystal orientation described below means that the (001) plane of at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals is oriented in the normal direction dn to the surface of the piezoelectric thin film 3 .

[0036] The piezoelectric thin film 3 is a crystalline film formed by a vapor phase growth method or a solution method, and is likely to have the above-mentioned crystal orientation. On the other hand, a bulk of a piezoelectric body having the same composition as the piezoelectric thin film 3 tends to be less likely to have the above-mentioned crystal orientation than the piezoelectric thin film 3. This is because the bulk of the piezoelectric body is a sintered body (ceramic) of powder containing essential elements of the piezoelectric body, and it is difficult to control the structure and orientation of the many crystals that make up the sintered body. The bulk of the piezoelectric body contains Fe, and therefore the resistivity of the bulk of the piezoelectric body is lower than that of the piezoelectric thin film 3. As a result, leakage current is likely to occur in the bulk of the piezoelectric body. Therefore, it is difficult to polarize the bulk of the piezoelectric body by applying a high electric field, and it is difficult for the bulk of the piezoelectric body to have the same piezoelectric properties as the piezoelectric thin film.

[0037] The metal oxide contained in the piezoelectric thin film 3 may be represented by the following Chemical Formula 1. The following Chemical Formula 1 is substantially the same as the following Chemical Formula 1a and the following Chemical Formula 1b. In the following Chemical Formula 1 and Chemical Formula 1a, M is Ga. 1-δ Co δ In Chemical Formula 1a and Chemical Formula 1b, (Bi 1-α K α ) x Bi y+z corresponds to the A site of the unit cell uc of the perovskite oxide (ABO3). x (Ti 1-β Mg β ) y (Fe 1-γ M γ )z corresponds to the B site of the unit cell uc of the perovskite oxide. x (Ti 1-β Mg β ) y (Fe 1-γ (Ga 1-δ Co δ ) γ ) z corresponds to the B site of a unit cell uc of a perovskite oxide. When the metal oxide is represented by the following chemical formula 1, the piezoelectric thin film 3 is likely to contain at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals, the crystal is likely to have the above-mentioned crystal orientation, and the piezoelectric thin film 3 is likely to have excellent piezoelectric properties and ferroelectricity. x(Bi 1-α K α )TiO3‐yBi(Ti 1-β Mg β )O3‐zBi(Fe 1-γ M γ )O3(1) (Bi 1-α K α ) x Bi y+z Ti x (Ti 1-β Mg β ) y (Fe 1-γ M γ ) z O 3±ε (1a) (Bi 1-α K α ) x Bi y+z Ti x (Ti 1-β Mg β ) y (Fe 1-γ (Ga 1-δ Co δ ) γ ) z O 3±ε (1b)

[0038] The units of x, y, z, α, β, γ, δ, and ε in each of the above chemical formulas are moles or molar ratios. Each of x, y, and z is a positive real number. x+y+z is 1.000. x in each chemical formula is greater than 0.000 and less than 1.000. y in each chemical formula is greater than 0.000 and less than 1.000. z in each chemical formula is greater than 0.000 and less than 1.000. As long as the crystal structure of the perovskite oxide is maintained, α in each chemical formula is greater than 0.000 and less than 1.000. As long as the crystal structure of the perovskite oxide is maintained, β in each chemical formula is greater than 0.000 and less than 1.000. For example, α may be 0.500 and β may be 0.500. In each chemical formula, γ is 0.050 or more and 0.400 or less. In each chemical formula, δ is 0.000 or more and 1.000 or less. When γ in each chemical formula is greater than or equal to 0.050 and less than or equal to 0.400, the piezoelectric thin film 3 is more likely to contain at least one crystal selected from the group consisting of tetragonal and orthogonal crystals, the crystal is more likely to have the above-mentioned crystal orientation, and the piezoelectric thin film 3 is more likely to have excellent piezoelectric properties and ferroelectricity.

[0039] The total amount of substance of Bi and K in the metal oxide may be expressed as [A] moles, and the total amount of substance of Ti, Mg, Fe, and element M in the metal oxide may be expressed as [B] moles, and [A] / [B] may be 1.000. As long as the metal oxide can have a perovskite structure, [A] / [B] may be a value other than 1.000. That is, [A] / [B] may be less than 1.000 or may be greater than 1.000. ε in Chemical Formula 1a and Chemical Formula 1b is 0.000 or more. As long as the metal oxide can have a perovskite structure, ε may be a value other than 0.000. For example, ε may be greater than 0.000 and less than 1.000. ε may be calculated from the valence of each of the elements in the A site and the B site of the perovskite structure. The valence of each element may be measured by X-ray photoelectron spectroscopy (XPS).

[0040] In the following, (Bi 1-α K α)TiO3 is written as BKT. Bi(Ti 1-β Mg β )O3 is abbreviated as BMT. BiFe 1-γ M γ BiFeO3 is expressed as BFMO. BiFeO3 is expressed as BFO. A metal oxide having a composition expressed as the sum of BKT and BMT is expressed as BKT-BMT. A metal oxide having a composition expressed as the sum of BKT, BMT, and BFO is expressed as BKT-BMT-BFO. A metal oxide having a composition expressed by the above chemical formula 1 is expressed as xBKT-yBMT-zBFMO. The crystals of BKT, BMT, BFMO, BFO, BKT-BMT, BKT-BMT-BFO, and xBKT-yBMT-zBFMO each have a perovskite structure.

[0041] Both bismuth gallate (BiGaO3; BGO) and bismuth cobaltate (BiCoO3; BCO) are perovskite oxides. The c / a of the crystals (tetragonal) of bismuth gallate and bismuth cobaltate is larger than the c / a of the crystals (rhombohedral) of BFO. In xBKT-yBMT-zBFMO, a part of BFO is replaced by one or both of BGO and BCO, so the c / a of the crystals of xBKT-yBMT-zBFMO tends to be larger than the c / a of conventional BKT-BMT-BFO. As a result, the piezoelectric thin film 3 including xBKT-yBMT-zBFMO can have excellent piezoelectric and ferroelectric properties.

[0042] The crystal of BKT is tetragonal at room temperature, and BKT is a ferroelectric. The crystal of BMT is rhombohedral at room temperature, and BMT is a ferroelectric. The crystal of BFO is rhombohedral at room temperature, and BFO is a ferroelectric. A thin film made of BKT-BMT is tetragonal at room temperature. The c / a of the tetragonal crystal of BKT-BMT tends to be larger than the c / a of BKT. A thin film made of BKT-BMT has superior ferroelectric properties compared to a thin film made of BKT and a thin film made of BMT. A thin film made of xBKT-yBMT-zBFMO tends to be at least one of tetragonal and orthorhombic at room temperature. The c / a of xBKT-yBMT-zBFMO tends to be larger than the c / a of BKT-BMT and BKT-BMT-BFO. A thin film made of xBKT-yBMT-zBFMO has superior ferroelectricity compared to a thin film made of BKT-BMT or BKT-BMT-BFO. In other words, a piezoelectric thin film 3 containing xBKT-yBMT-zBFMO is likely to become a ferroelectric thin film. It is presumed that the ferroelectricity of the piezoelectric thin film 3 is due to the fact that the composition of xBKT-yBMT-zBFMO has a morphotropic phase boundary (MPB). However, since the piezoelectric thin film 3 belongs to the tetragonal or orthorhombic crystal system, it is presumed that the ferroelectricity of the piezoelectric thin film 3 is not simply due to the MPB. The ferroelectricity of the piezoelectric thin film 3 allows the piezoelectric thin film 3 to have a large d 33,f In contrast to the piezoelectric thin film 3, the crystals contained in the bulk of xBKT-yBMT-zBFMO are pseudocubic, and the bulk of xBKT-yBMT-zBFMO tends to be less likely to have the above-mentioned crystal orientation and ferroelectricity than the piezoelectric thin film 3.

[0043] The composition of xBKT-yBMT-zBFMO may be expressed based on a three-dimensional coordinate system. As shown in FIG. 4, the three-dimensional coordinate system is composed of an X axis, a Y axis, and a Z axis. Any coordinate in the coordinate system is expressed as (X, Y, Z). The coordinates (x, y, z) in the coordinate system indicate x, y, and z in the above chemical formula 1. The sum of x, y, and z in chemical formula 1 is 1, and x, y, and z are all positive real numbers. Therefore, the coordinates (x, y, z) are located inside a triangle drawn by a dotted line in a plane represented by X+Y+Z=1. In other words, the coordinates (x, y, z) are located inside a triangle whose vertices are coordinates (1,0,0), coordinates (1,1,0), and coordinates (0,0,1). This triangle is a triangular coordinate system, and in the triangular coordinate system, X+Y+Z is 1. The triangular coordinate system is shown in FIG. 5. The triangular coordinate system includes coordinates A, B, C, and D in addition to coordinates (x, y, z). That is, coordinates (x, y, z), coordinates A, B, C, D, E, and F are all located within a plane represented by X+Y+Z=1. Coordinate A is (0.250, 0.005, 0.700). Coordinate B is (0.450, 0.250, 0.300). Coordinate C is (0.200, 0.500, 0.300). Coordinate D is (0.005, 0.250, 0.700). The coordinates (x, y, z) indicating x, y, and z in Chemical Formula 1 may be located within a rectangle whose vertices are coordinates A, B, C, and D. When the coordinates (x, y, z) are within the rectangle ABCD, the composition of xBKT-yBMT-zBFMO is likely to have MPB, and the piezoelectric properties and ferroelectricity of the piezoelectric thin film 3 are likely to be improved. When x is equal to y, the coordinates (x, y, z) are located on the line passing through the coordinates (0.500, 0.500, 0.000) and the coordinates (0.000, 0.000, 1.000). When x is equal to y, the composition of xBKT-yBMT-zBFMO is likely to have MPB, and the piezoelectric properties and ferroelectricity of the piezoelectric thin film 3 are likely to be improved.

[0044] x may be 0.050 or more and 0.450 or less, or 0.100 or more and 0.350 or less, y may be 0.050 or more and 0.500 or less, or 0.100 or more and 0.350 or less, and z may be 0.300 or more and 0.700 or less. When x, y and z are in the above ranges and x+y+z is 1, the composition xBKT-yBMT-zBFMO is likely to have MPB, and the piezoelectric properties and ferroelectricity of the piezoelectric thin film 3 are likely to be improved.

[0045] For example, the thickness of the piezoelectric thin film 3 may be 10 nm to 10 μm, 0.3 μm to 10 μm, 0.3 μm to 5 μm, 0.5 μm to 5 μm, 0.3 μm to 3 μm, or 0.5 μm to 3 μm. 2 More than 500mm 2 The areas of the crystalline substrate 1, the first intermediate layer 5, the first electrode layer 2, the second intermediate layer 6, and the second electrode layer 4 may be the same as the area of ​​the piezoelectric thin film 3 or may be different.

[0046] For example, the composition of the piezoelectric thin film 3 may be analyzed by X-ray fluorescence spectroscopy (XRF) or inductively coupled plasma (ICP) optical emission spectroscopy. The crystal structure and crystal orientation of the piezoelectric thin film 3 may be identified by X-ray diffraction (XRD).

[0047] For example, the piezoelectric thin film 3 may be formed by the following method.

[0048] A target having the same composition as that of the piezoelectric thin film 3 may be used as the raw material of the piezoelectric thin film 3. The target is prepared as follows.

[0049] As the starting materials, for example, powders of bismuth oxide (Bi2O3), potassium carbonate (K2CO3), titanium oxide (TiO2), magnesium oxide (MgO), iron oxide (Fe2O3), and oxide of element M may be used. The oxide of element M may be at least one oxide selected from the group consisting of gallium oxide (Ga2O3) and cobalt oxide (CO2O3). Instead of the above oxides, substances that become oxides by sintering, such as carbonates or oxalates, may be used as the starting materials. After these starting materials are sufficiently dried at 100°C or higher, each starting material is weighed so that the substance amounts (molar ratios) of Bi, K, Ti, Mg, Fe, and element M are within the ranges specified in the above Chemical Formula 1, Chemical Formula 1a, or Chemical Formula 1b. In the vapor phase epitaxy described later, Bi and K in the target are more likely to volatilize than other elements. Therefore, the molar ratio of Bi in the target may be adjusted to a higher value than the molar ratio of Bi in the piezoelectric thin film 3. The molar ratio of K in the target may be adjusted to a higher value than the molar ratio of K in the piezoelectric thin film 3.

[0050] The weighed starting materials are thoroughly mixed in an organic solvent or water. The mixing time may be 5 hours or more and 20 hours or less. The mixing means may be a ball mill. After the mixed starting materials are thoroughly dried, the starting materials are molded in a press. The molded starting materials are calcinated to obtain a calcine. The calcine temperature may be 750°C or more and 900°C or less. The calcine time may be 1 hour or more and 3 hours or less. The calcine is pulverized in an organic solvent or water. The pulverization time may be 5 hours or more and 30 hours or less. The pulverization means may be a ball mill. After drying the pulverized calcine, the calcine to which a binder solution has been added is granulated to obtain a calcine powder. The calcine powder is press molded to obtain a block-shaped molded body.

[0051] The binder in the block-shaped molded body is volatilized by heating the molded body. The heating temperature may be 400° C. or more and 800° C. or less. The heating time may be 2 hours or more and 4 hours or less. The molded body is then sintered to obtain a target. The sintering temperature may be 800° C. or more and 1100° C. or less. The sintering time may be 2 hours or more and 4 hours or less. The heating rate and the cooling rate of the molded body in the sintering process may be, for example, 50° C. / hour or more and 300° C. / hour or less. The average grain size of the crystal grains of the metal oxide contained in the target may be, for example, 1 μm or more and 20 μm or less.

[0052] The piezoelectric thin film 3 may be formed by a vapor phase growth method using the above target. In the vapor phase growth method, elements constituting the target are evaporated in a vacuum atmosphere. The evaporated elements are attached and deposited on the surface of any one of the second intermediate layer 6, the first electrode layer 2, or the crystalline substrate 1, thereby growing the piezoelectric thin film 3. The vapor phase growth method may be, for example, a sputtering method, an electron beam evaporation method, a chemical vapor deposition method, or a pulsed-laser deposition method. Hereinafter, the pulsed-laser deposition method is referred to as a PLD method. By using these vapor phase growth methods, it is possible to form a piezoelectric thin film 3 that is dense at the atomic level, and segregation of elements in the piezoelectric thin film 3 is suppressed. The excitation source differs depending on the type of vapor phase growth method. The excitation source of the sputtering method is Ar plasma. The excitation source of the electron beam evaporation method is an electron beam. The excitation source of the PLD method is a laser beam (for example, an excimer laser). When these excitation sources are irradiated onto a target, the elements that make up the target evaporate.

[0053] Among the above vapor phase growth methods, the PLD method is relatively superior in the following respects. In the PLD method, the elements constituting the target can be instantly and uniformly converted into plasma by a pulsed laser. Therefore, it is easy to form a piezoelectric thin film 3 having a composition substantially or completely the same as that of the target. Furthermore, in the PLD method, the thickness of the piezoelectric thin film 3 can be easily controlled by changing the number of laser pulse shots.

[0054] The piezoelectric thin film 3 may be an epitaxial film. That is, the piezoelectric thin film 3 may be formed by epitaxial growth. A piezoelectric thin film 3 having excellent crystal orientation is likely to be formed by epitaxial growth. When the piezoelectric thin film 3 is formed by the PLD method, the piezoelectric thin film 3 is likely to be formed by epitaxial growth.

[0055] In the PLD method, the piezoelectric thin film 3 may be formed while heating the crystalline substrate 1 and the first electrode layer 2 in a vacuum chamber. The temperature (film formation temperature) of the crystalline substrate 1 and the first electrode layer 2 may be, for example, 300° C. or higher and 800° C. or lower, 500° C. or higher and 700° C. or lower, or 500° C. or higher and 600° C. or lower. The higher the film formation temperature, the more improved the cleanliness of the surface of the crystalline substrate 1 or the first electrode layer 2 is, the higher the crystallinity of the piezoelectric thin film 3 is, and the more likely it is that the orientation of the (001) plane in the piezoelectric thin film 3 is to be increased. If the film formation temperature is too high, Bi or K is likely to be desorbed from the piezoelectric thin film 3, making it difficult to control the composition of the piezoelectric thin film 3.

[0056] In the PLD method, the oxygen partial pressure in the vacuum chamber may be, for example, greater than 10 mTorr and less than 400 mTorr, greater than 15 mTorr and less than 300 mTorr, or greater than 20 mTorr and less than 200 mTorr. In other words, the oxygen partial pressure in the vacuum chamber may be, for example, greater than 1 Pa and less than 53 Pa, greater than 2 Pa and less than 40 Pa, or greater than 3 Pa and less than 30 Pa. By maintaining the oxygen partial pressure within the above range, Bi, K, Ti, Mg, Fe, and element M deposited on the crystalline substrate 1 are likely to be sufficiently oxidized. If the oxygen partial pressure is too high, the growth rate of the piezoelectric thin film 3 is likely to decrease, and the orientation degree of the (001) plane in the piezoelectric thin film 3 is likely to decrease.

[0057] Other parameters controlled in the PLD method include, for example, the laser oscillation frequency and the distance between the substrate and the target. By controlling these parameters, it is easy to control the crystal structure and crystal orientation of the piezoelectric thin film 3. For example, when the laser oscillation frequency is 10 Hz or less, the degree of orientation of the (001) plane in the piezoelectric thin film 3 is easy to increase.

[0058] After the piezoelectric thin film 3 is grown, the piezoelectric thin film 3 may be annealed (heated). The temperature of the piezoelectric thin film 3 in the annealing (annealing temperature) may be, for example, 300° C. or higher and 1000° C. or lower, 600° C. or higher and 1000° C. or lower, or 850° C. or higher and 1000° C. or lower. Annealing the piezoelectric thin film 3 tends to further improve the piezoelectric characteristics of the piezoelectric thin film 3. In particular, annealing at 850° C. or higher and 1000° C. or lower tends to improve the piezoelectric characteristics of the piezoelectric thin film 3. However, annealing is not essential.

[0059] For example, the crystalline substrate 1 may be a substrate made of a single crystal of Si, or a substrate made of a single crystal of a compound semiconductor such as GaAs. The crystalline substrate 1 may be a substrate made of a single crystal of an oxide such as MgO or a perovskite oxide (for example, SrTiO3). For example, the thickness of the crystalline substrate 1 may be 10 μm or more and 1000 μm or less. When the crystalline substrate 1 has conductivity, the crystalline substrate 1 functions as an electrode, so that the first electrode layer 2 may not be required. That is, for example, the crystalline substrate 1 having conductivity may be a single crystal of SrTiO3 doped with niobium (Nb). As the crystalline substrate 1, a silicon-on-insulator (SOI) substrate may be used.

[0060] The crystal orientation of the crystalline substrate 1 may be the same as the normal direction of the surface of the crystalline substrate 1. In other words, the surface of the crystalline substrate 1 may be parallel to the lattice plane of the crystalline substrate 1. The crystalline substrate 1 may be a uniaxially oriented substrate. For example, one lattice plane selected from the group consisting of the (100) plane, the (001) plane, the (110) plane, the (101) plane, and the (111) plane may be parallel to the surface of the crystalline substrate 1. When the (100) plane of the crystalline substrate 1 (e.g., Si) is parallel to the surface of the crystalline substrate 1, the (001) plane of the crystal in the piezoelectric thin film 3 is likely to be oriented in the normal direction dn of the surface of the piezoelectric thin film 3.

[0061] As described above, the first intermediate layer 5 may be disposed between the crystalline substrate 1 and the first electrode layer 2. For example, the first intermediate layer 5 may contain at least one selected from the group consisting of titanium (Ti), chromium (Cr), titanium oxide (TiO2), silicon oxide (SiO2), and zirconium oxide (ZrO2). The first intermediate layer 5 facilitates adhesion of the first electrode layer 2 to the crystalline substrate 1. The first intermediate layer 5 may be crystalline. The lattice plane of the first intermediate layer 5 may be oriented in the normal direction to the surface of the crystalline substrate 1. Both the lattice plane of the crystalline substrate 1 and the lattice plane of the first intermediate layer 5 may be oriented in the normal direction to the surface of the crystalline substrate 1. The method for forming the first intermediate layer 5 may be a sputtering method, a vacuum deposition method, a printing method, a spin coating method, or a sol-gel method.

[0062] The first intermediate layer 5 may contain ZrO2 and an oxide of a rare earth element. By containing ZrO2 and an oxide of a rare earth element, the first electrode layer 2 made of platinum crystals is easily formed on the surface of the first intermediate layer 5, and the (002) plane of the platinum crystal is aligned in the normal direction D of the surface of the first electrode layer 2. NThe (200) plane of the platinum crystal is likely to be oriented in the in-plane direction of the surface of the first electrode layer 2. The rare earth element may be at least one element selected from the group consisting of scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). The first intermediate layer 5 may be made of yttria-stabilized zirconia (ZrO2 with Y2O3 added). Since the first intermediate layer 5 is made of yttria-stabilized zirconia, the first electrode layer 2 made of platinum crystals is easily formed on the surface of the first intermediate layer 5, and the (002) plane of the platinum crystals is aligned in the normal direction D of the surface of the first electrode layer 2. N and the (200) plane of the platinum crystal is likely to be oriented in the in-plane direction of the surface of the first electrode layer 2. For the same reason, the first intermediate layer 5 may have a first layer made of ZrO2 and a second layer made of Y2O3. The first layer may be laminated directly on the surface of the crystalline substrate 1, the second layer may be laminated directly on the surface of the first layer, and the first electrode layer 2 may be laminated directly on the surface of the second layer.

[0063] For example, the first electrode layer 2 may be made of at least one metal selected from the group consisting of platinum (Pt), palladium (Pd), rhodium (Rh), gold (Au), ruthenium (Ru), iridium (Ir), molybdenum (Mo), titanium (Ti), tantalum (Ta), and nickel (Ni). The first electrode layer 2 may be made of a conductive metal oxide such as strontium ruthenate (SrRuO3), lanthanum nickelate (LaNiO3), or lanthanum strontium cobaltate ((La,Sr)CoO3). The first electrode layer 2 may be crystalline. The lattice plane of the first electrode layer 2 may be oriented in the normal direction to the surface of the crystalline substrate 1. The lattice plane of the first electrode layer 2 may be approximately or completely parallel to the surface of the crystalline substrate 1. Both the lattice plane of the crystalline substrate 1 and the lattice plane of the first electrode layer 2 may be oriented in the normal direction to the surface of the crystalline substrate 1. The lattice plane of the first electrode layer 2 may be substantially or completely parallel to the lattice plane of the perovskite oxide oriented in the piezoelectric thin film 3. For example, the thickness of the first electrode layer 2 may be 1 nm or more and 1.0 μm or less. The method for forming the first electrode layer 2 may be a sputtering method, a vacuum deposition method, a printing method, a spin coating method, or a sol-gel method. In the case of the printing method, the spin coating method, or the sol-gel method, the first electrode layer 2 may be subjected to a heat treatment (annealing) in order to enhance the crystallinity of the first electrode layer 2.

[0064] The first electrode layer 2 may include platinum crystals. The first electrode layer 2 may be made of only platinum crystals. The platinum crystals are cubic crystals having a face-centered cubic lattice structure. The (002) plane of the platinum crystals is aligned in the normal direction D of the surface of the first electrode layer 2. NThe (002) plane of the platinum crystal may be oriented in the in-plane direction of the surface of the first electrode layer 2, and the (200) plane of the platinum crystal may be oriented in the in-plane direction of the surface of the first electrode layer 2. In other words, the (002) plane of the platinum crystal may be substantially or completely parallel to the surface of the first electrode layer 2, and the (200) plane of the platinum crystal may be substantially or completely perpendicular to the surface of the first electrode layer 2. When the (002) plane and the (200) plane of the platinum crystal constituting the first electrode layer 2 have the above-mentioned orientation, the piezoelectric thin film 3 is likely to grow epitaxially on the surface of the first electrode layer 2, and the lattice stress caused by the lattice mismatch between the first electrode layer 2 and the piezoelectric thin film 3 is likely to act on the piezoelectric thin film 3. The lattice stress may be a compressive stress in the in-plane direction of the surface of the piezoelectric thin film 3. As a result, the piezoelectric thin film 3 is likely to include at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals, and the (001) plane of the crystal is likely to be preferentially oriented in the normal direction dn of the surface of the piezoelectric thin film 3. As a result, the piezoelectric thin film element 10 tends to have excellent piezoelectric properties and ferroelectricity.

[0065] The second intermediate layer 6 may be disposed between the first electrode layer 2 and the piezoelectric thin film 3. The second intermediate layer 6 may contain at least one compound selected from the group consisting of SrRuO3, LaNiO3, and (La,Sr)CoO3. The second intermediate layer 6 facilitates adhesion of the piezoelectric thin film 3 to the first electrode layer 2. The second intermediate layer 6 may be crystalline. When the second intermediate layer 6 contains at least one of SrRuO3 and LaNiO3, lattice stress caused by lattice mismatch between the second intermediate layer 6 and the piezoelectric thin film 3 is likely to act on the piezoelectric thin film 3. The lattice stress may be a compressive stress in the in-plane direction of the surface of the piezoelectric thin film 3. As a result, the piezoelectric thin film 3 is likely to contain at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals, and the (001) plane of the crystal is likely to be preferentially oriented in the normal direction dn of the surface of the piezoelectric thin film 3. As a result, the piezoelectric thin film element 10 is likely to have excellent piezoelectric properties and ferroelectricity. The lattice plane of the second intermediate layer 6 is aligned in the normal direction D N Both the lattice plane of the crystalline substrate 1 and the lattice plane of the second intermediate layer 6 may be oriented in the normal direction D NThe second intermediate layer 6 may be formed by a sputtering method, a vacuum deposition method, a printing method, a spin coating method, or a sol-gel method.

[0066] The second electrode layer 4 may be made of at least one metal selected from the group consisting of, for example, Pt, Pd, Rh, Au, Ru, Ir, Mo, Ti, Ta, and Ni. The second electrode layer 4 may be made of at least one conductive metal oxide selected from the group consisting of, for example, LaNiO3, SrRuO3, and (La,Sr)CoO3. The second electrode layer 4 may be crystalline. The lattice plane of the second electrode layer 4 may be oriented in the normal direction dn of the surface of the piezoelectric thin film 3. The lattice plane of the second electrode layer 4 may be approximately or completely parallel to the surface of the piezoelectric thin film 3. The lattice plane of the second electrode layer 4 may be approximately or completely parallel to the (001) plane oriented in the piezoelectric thin film 3. For example, the thickness of the second electrode layer 4 may be 1 nm or more and 1.0 μm or less. The method for forming the second electrode layer 4 may be a sputtering method, a vacuum deposition method, a printing method, a spin coating method, or a sol-gel method. In the case of the printing method, the spin coating method, or the sol-gel method, in order to enhance the crystallinity of the second electrode layer 4, a heat treatment (annealing) of the second electrode layer 4 may be performed.

[0067] A third intermediate layer may be disposed between the piezoelectric thin film 3 and the second electrode layer 4. The second electrode layer 4 is easily attached to the piezoelectric thin film 3 by the third intermediate layer. Due to the lattice mismatch between the crystalline third intermediate layer and the piezoelectric thin film 3, the above-mentioned lattice stress is easily applied to the piezoelectric thin film 3. As a result, the piezoelectric thin film 3 is likely to contain at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals, and the (001) plane of the crystal is likely to be preferentially oriented in the normal direction dn to the surface of the piezoelectric thin film 3. As a result, the piezoelectric thin film element 10 is likely to have excellent piezoelectric characteristics and ferroelectricity. The composition, crystal structure, and formation method of the third intermediate layer may be the same as those of the second intermediate layer 6.

[0068] At least a part or the entire surface of the piezoelectric thin film element 10 may be covered with a protective film. By covering the piezoelectric thin film element 10 with a protective film, for example, the moisture resistance of the piezoelectric thin film element 10 is improved.

[0069] The piezoelectric thin film element according to the present embodiment has a wide variety of applications. For example, the piezoelectric thin film element may be a part or the whole of one device selected from the group consisting of a piezoelectric actuator, a piezoelectric sensor, a piezoelectric transducer, a piezoelectric microphone, a harvester, an oscillator, a resonator, an acoustic multilayer film, a pyroelectric element, and a filter. For example, the piezoelectric actuator may be used for haptics. That is, the piezoelectric actuator may be used in various devices that require feedback by skin sensation (tactile sensation). For example, the device that requires feedback by skin sensation may be a wearable device, a touch pad, a display, or a game controller. For example, the piezoelectric actuator may be used in a head assembly, a head stack assembly, or a hard disk drive. For example, the piezoelectric actuator may be used in a printer head or an inkjet printer device. For example, the piezoelectric actuator may be used in a piezoelectric switch. For example, the piezoelectric sensor or the piezoelectric transducer may be used in a gyro sensor, a pressure sensor, a pulse wave sensor, an ultrasonic sensor, an ultrasonic transducer, an infrared sensor, or a shock sensor. The ultrasonic transducer may be a Piezoelectric Micromachined Ultrasonic Transducer (PMUT). The product to which the piezoelectric micromachined ultrasonic transducer is applied may be a biometric sensor such as a fingerprint sensor and an ultrasonic blood vessel authentication sensor, a sensor for medical or health care, or a Time of Flight (ToF) sensor. For example, the filter may be a BAW (Bulk Acoustic Wave) filter or a SAW (Surface Acoustic Wave) filter. Each of the piezoelectric thin film elements described above may be a part or the whole of a Micro Electro Mechanical System (MEMS). Each of the piezoelectric thin film elements described above may be a wearable device or a portable device.

[0070] The piezoelectric transducer according to this embodiment includes the piezoelectric thin film or piezoelectric thin film element described above. FIG. 6 shows a schematic cross section of an ultrasonic transducer 10a, which is an example of a piezoelectric transducer. The cross section of the ultrasonic transducer 10a is approximately or completely parallel to the normal direction dn of the surface of the piezoelectric thin film 3. The ultrasonic transducer 10a may include substrates 1a and 1b, a first electrode layer 2 disposed on the substrates 1a and 1b, a piezoelectric thin film 3 overlapping the first electrode layer 2, and a second electrode layer 4 overlapping the piezoelectric thin film 3. An acoustic cavity 1c may be provided below the piezoelectric thin film 3. An ultrasonic signal is transmitted or received by the deflection or vibration of the piezoelectric thin film 3. A first intermediate layer may be interposed between the substrates 1a and 1b and the first electrode layer 2. A second intermediate layer may be interposed between the first electrode layer 2 and the piezoelectric thin film 3. A second intermediate layer may be interposed between the piezoelectric thin film 3 and the second electrode layer 4. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0072] Example 1 A crystalline substrate made of a single crystal of Si was used to fabricate the piezoelectric thin film element of Example 1. The (100) plane of Si was parallel to the surface of the crystalline substrate. The crystalline substrate was a square of 20 mm x 20 mm. The thickness of the crystalline substrate was 500 μm.

[0073] In a vacuum chamber, a crystalline first intermediate layer made of ZrO2 and Y2O3 was formed on the entire surface of the crystalline substrate. The first intermediate layer was formed by a sputtering method. The thickness of the first intermediate layer was 30 nm.

[0074] In a vacuum chamber, a first electrode layer made of Pt crystals was formed on the entire surface of the first intermediate layer. The first electrode layer was formed by a sputtering method. The thickness of the first electrode layer was 200 nm. The temperature of the crystalline substrate during the formation of the first electrode layer (film formation temperature) was maintained at 500°C.

[0075] The X-ray diffraction (XRD) pattern of the first electrode layer was measured by out-of-plane measurement on the surface of the first electrode layer. The XRD pattern of the first electrode layer was measured by in-plane measurement on the surface of the first electrode layer. An X-ray diffractometer (SmartLab) manufactured by Rigaku Corporation was used to measure these XRD patterns. The measurement conditions were set so that each peak intensity in the XRD pattern was at least three orders of magnitude higher than the background intensity. The out-of-plane measurement detected a diffracted X-ray peak of the (002) plane of the Pt crystal. In other words, the (002) plane of the Pt crystal was oriented in the normal direction of the surface of the first electrode layer. The in-plane measurement detected a diffracted X-ray peak of the (200) plane of the Pt crystal. In other words, the (200) plane of the Pt crystal was oriented in the in-plane direction of the surface of the first electrode layer.

[0076] In the vacuum chamber, a piezoelectric thin film was formed on the entire surface of the first electrode layer. The piezoelectric thin film was formed by the PLD method. The thickness of the piezoelectric thin film was 2000 nm. The temperature (film formation temperature) of the crystalline substrate during the formation of the piezoelectric thin film was maintained at 500° C. The oxygen partial pressure in the vacuum chamber during the formation of the piezoelectric thin film was maintained at 10 Pa. A target (sintered body of raw material powder) was used as the raw material for the piezoelectric thin film. When the target was prepared, the compounding ratio of the raw material powder (bismuth oxide, potassium carbonate, titanium oxide, magnesium oxide, iron oxide, and gallium oxide) was adjusted according to the composition of the desired piezoelectric thin film. The composition of the desired piezoelectric thin film was represented by the following chemical formula 1A. That is, the composition of the target was represented by the following chemical formula 1A. The values ​​of x, y, z, α, β, and γ in the following chemical formula 1A were the values ​​shown in Table 1 below. x(Bi 1-α K α )TiO3‐yBi(Ti 1-β Mg β )O3‐zBi(Fe 1-γ Ga γ )O3(1A)

[0077] The composition of the piezoelectric thin film was analyzed by X-ray fluorescence analysis (XRF method). For the analysis, a PW2404 device manufactured by Philips Japan Ltd. was used. As a result of the analysis, the composition of the piezoelectric thin film of Example 1 was represented by the above chemical formula 1A, and the values ​​of x, y, z, α, β, and γ in the above chemical formula 1A were consistent with the values ​​shown in Table 1 below. In other words, the composition of the piezoelectric thin film was consistent with the composition of the target.

[0078] The XRD pattern of the piezoelectric thin film was measured by out-of-plane measurement on the surface of the piezoelectric thin film. The XRD pattern of the piezoelectric thin film was measured by in-plane measurement on the surface of the piezoelectric thin film. The measuring device and measuring conditions for the XRD pattern were the same as above. The XRD pattern of the piezoelectric thin film showed that the piezoelectric thin film was composed of perovskite-type oxide crystals. The lattice constant c of the above crystals in the normal direction to the surface of the piezoelectric thin film was measured by out of plane measurement. Lattice constant c can be rephrased as the spacing between lattice planes parallel to the surface of the piezoelectric thin film. The lattice constants a and b of the above crystals in the direction parallel to the surface of the piezoelectric thin film were measured by in plane measurement. Lattice constants a and b can be rephrased as the spacing between lattice planes perpendicular to the surface of the piezoelectric thin film. a and b were approximately equal to each other. Both a and b were smaller than c. In other words, at least a portion of the above crystals contained in the piezoelectric thin film were tetragonal with c / a greater than 1. The out of plane measurement detected the peak of the diffracted X-rays of the (001) plane of the perovskite oxide crystal. Based on the XRD pattern, the orientation degree of the (001) plane of the crystal was calculated. As mentioned above, the orientation degree of the (001) plane is 100×I 1(001) / (I 1(001) +I 1(110) +I 1(111) ) The degree of orientation of the (001) plane in the normal direction dn to the surface of the piezoelectric thin film was 90% or more. In other words, the (001) plane of the crystal was preferentially oriented in the normal direction dn to the surface of the piezoelectric thin film. Lattice planes that are preferentially oriented in the normal direction dn to the surface of the piezoelectric thin film (lattice planes with an orientation degree of 90% or more) are referred to as "oriented planes" in the tables below.

[0079] In the above manner, a laminate was produced that was composed of a crystalline substrate, a first intermediate layer overlapping the crystalline substrate, a first electrode layer overlapping the first intermediate layer, and a piezoelectric thin film overlapping the first electrode layer. The following steps were then carried out using this laminate.

[0080] In a vacuum chamber, a second electrode layer made of Pt was formed on the entire surface of the piezoelectric thin film. The second electrode layer was formed by a sputtering method. The temperature of the crystalline substrate during the formation of the second electrode layer was maintained at 500°C. The thickness of the second electrode layer was 200 nm.

[0081] Through the above steps, a laminate was produced that was composed of a crystalline substrate, a first intermediate layer overlapping the crystalline substrate, a first electrode layer overlapping the first intermediate layer, a piezoelectric thin film overlapping the first electrode layer, and a second electrode layer overlapping the piezoelectric thin film. The laminate structure on the crystalline substrate was then patterned by photolithography. After patterning, the laminate was cut by dicing.

[0082] Through the above steps, a rectangular piezoelectric thin film element of Example 1 was obtained. The piezoelectric thin film element was composed of a crystalline substrate, a first intermediate layer overlapping the crystalline substrate, a first electrode layer overlapping the first intermediate layer, a piezoelectric thin film overlapping the first electrode layer, and a second electrode layer overlapping the piezoelectric thin film. The area of ​​the movable part of the piezoelectric thin film was 20 mm x 1.0 mm.

[0083] [Piezoelectric strain constant d 33,f Measurement of Using the piezoelectric thin film element of Example 1, the piezoelectric strain constant d 33,f was measured. 33,f The measurement was performed using an apparatus that combined an atomic force microscope (AFM) and a ferroelectric evaluation system. The atomic force microscope was an SPA-400 manufactured by Seiko Instruments Inc., and the ferroelectric evaluation system was an FCE manufactured by Toyo Corporation. 33,f The frequency of the AC electric field (AC voltage) in the measurement was 5 Hz. The maximum voltage applied to the piezoelectric thin film was 20 V.33,f The unit of is pm / V. 33,f is shown in Table 1 below.

[0084] (Examples 2 to 18 and Comparative Examples 1 to 4) When preparing the targets of Examples 2 to 18 and Comparative Examples 1 to 4, the compounding ratio of the raw material powders (bismuth oxide, potassium carbonate, titanium oxide, magnesium oxide, iron oxide, and gallium oxide) was adjusted according to the composition of the desired piezoelectric thin film. As a raw material for the target of Comparative Example 1, potassium carbonate was not used. As a raw material for the target of Comparative Example 2, magnesium oxide was not used. As the raw material for the target of Comparative Example 3, gallium oxide was not used. As the raw material for the target of Comparative Example 4, no iron oxide was used. The piezoelectric thin film elements of Examples 2 to 18 and Comparative Examples 1 to 4 were each produced in the same manner as in Example 1, except that the compositions of the targets used to form the piezoelectric thin films were different.

[0085] The XRD patterns of the first electrode layers of Examples 2 to 18 and Comparative Examples 1 to 4 were measured by the same method as in Example 1. In all of Examples 2 to 18 and Comparative Examples 1 to 4, the (002) plane of the Pt crystals constituting the first electrode layer was oriented in the normal direction to the surface of the first electrode layer, and the (200) plane of the Pt crystals was oriented in the in-plane direction of the surface of the first electrode layer.

[0086] The composition of the piezoelectric thin film of each of Examples 2 to 18 and Comparative Examples 1 to 4 was analyzed by the same method as in Example 1. In each of Examples 2 to 18 and Comparative Examples 1 to 4, the composition of the piezoelectric thin film was consistent with the composition of the target (above Chemical Formula 1A). In each of Examples 2 to 18 and Comparative Examples 1 to 4, the values ​​of x, y, z, α, β, γ, and δ in Chemical Formula 1A were as shown in Table 1 below. x, y, and z of each of Examples 1 to 14 are shown in FIG. 5 (triangular coordinate system) as coordinates (x, y, z). Coordinate A in FIG. Coordinate B in FIG. Coordinate C in FIG. Coordinate D in FIG. Coordinate E in FIG. Coordinate F in FIG. The coordinate G in FIG. Coordinate H in FIG. Coordinate I in FIG. Coordinate J in FIG. The coordinate K in FIG. The coordinate L in FIG. Coordinate M in FIG. The coordinate O in FIG.

[0087] The XRD patterns of the piezoelectric thin films of Examples 2 to 18 and Comparative Examples 1 to 4 were measured by the same method as in Example 1. The XRD patterns of Examples 2 to 18 and Comparative Examples 1 to 4 all showed that the piezoelectric thin films were composed of perovskite oxide crystals. In each of Examples 2 to 18 and Comparative Examples 1 to 4, at least a part of the crystals contained in the piezoelectric thin films were tetragonal. In each of Examples 2 to 18 and Comparative Examples 1 to 4, the (001) plane of the crystals was preferentially oriented in the normal direction to the surface of the piezoelectric thin film.

[0088] The piezoelectric strain constant d of the piezoelectric thin film of each of Examples 2 to 18 and Comparative Examples 1 to 4 was measured by the same method as in Example 1. 33,f was measured. 33,f is shown in Table 1 below.

[0089] Comparative Example 5 The target of Comparative Example 5 did not contain bismuth. The target of Comparative Example 5 had a composition represented by the following Chemical Formula 5. Each numerical value in the following Chemical Formula 5 represents a molar ratio. The thin film and thin film element of Comparative Example 5 were produced in the same manner as in Example 1, except that the composition of the target used to form the thin film was different. Analysis and measurement were carried out on the thin film and thin film element of Comparative Example 5 in the same manner as in Example 1. In Comparative Example 5, the (002) plane of the Pt crystal constituting the first electrode layer was also oriented in the normal direction to the surface of the first electrode layer, and the (200) plane of the Pt crystal was oriented in the in-plane direction of the surface of the first electrode layer. The composition of the thin film of Comparative Example 5 was consistent with the composition of the target of Comparative Example 5. The thin film of Comparative Example 5 was not a crystal having an oriented lattice plane, and did not have piezoelectric properties. 0.20MgTiO3-0.10K2O-0.20TiO2-0.50(Fe 0.9 Ga 0.1 )2O3(5)

[0090] [Table 1]

[0091] (Comparative Examples 6 to 8) The oxygen partial pressure in the vacuum chamber was maintained at 1 Pa during the formation of the piezoelectric thin film of Comparative Example 6. The oxygen partial pressure in the vacuum chamber during the formation of the piezoelectric thin film of Comparative Example 7 was maintained at 20 Pa. The oxygen partial pressure in the vacuum chamber during the formation of the piezoelectric thin film of Comparative Example 8 was maintained at 0.1 Pa. The piezoelectric thin film elements of Comparative Examples 6 to 8 were each produced in the same manner as in Example 9, except for the oxygen partial pressure in the process of forming the piezoelectric thin film.

[0092] The XRD patterns of the first electrode layers of Comparative Examples 6 to 8 were measured by the same method as in Example 1. In all of Comparative Examples 6 to 8, the (002) plane of the Pt crystals constituting the first electrode layer was oriented in the normal direction to the surface of the first electrode layer, and the (200) plane of the Pt crystals was oriented in the in-plane direction of the surface of the first electrode layer.

[0093] The composition of the piezoelectric thin film of each of Comparative Examples 6 to 8 was analyzed by the same method as in Example 1. In each of Comparative Examples 6 to 8, the composition of the piezoelectric thin film was consistent with the composition of the target. In other words, the composition of the piezoelectric thin film of each of Comparative Examples 6 to 8 was the same as the composition of the piezoelectric thin film of Example 9.

[0094] By the same method as in Example 1, the XRD patterns of the piezoelectric thin films of Comparative Examples 6 to 8 were measured. All of the XRD patterns of Comparative Examples 6 to 8 showed that the piezoelectric thin films were composed of perovskite-type oxide crystals. In all of Comparative Examples 6 to 8, at least a portion of the crystals contained in the piezoelectric thin film was tetragonal. In the case of Comparative Example 6, the (110) plane of the crystals in the piezoelectric thin film was preferentially oriented in the normal direction to the surface of the piezoelectric thin film. In the case of Comparative Example 7, the (111) plane of the crystals in the piezoelectric thin film was preferentially oriented in the normal direction to the surface of the piezoelectric thin film. In the case of Comparative Example 8, a specific lattice plane of the crystal in the piezoelectric thin film was not oriented in the normal direction to the surface of the piezoelectric thin film, that is, in the case of Comparative Example 8, the degree of orientation of all lattice planes was less than 50%.

[0095] The piezoelectric strain constant d of the piezoelectric thin film of each of Comparative Examples 6 to 8 was measured by the same method as in Example 1. 33,f was measured. 33,f is shown in Table 2 below.

[0096] [Table 2]

[0097] (Examples 19 and 20) In the case of Examples 19 and 20, the second intermediate layer was formed directly on the entire surface of the first electrode layer, and the piezoelectric thin film was formed directly on the entire surface of the second intermediate layer. The second intermediate layer of Example 19 was made of crystalline SrRuO3 and had a thickness of 50 nm. The second intermediate layer of Example 20 was made of crystalline LaNiO3. The thickness of the second intermediate layer of Example 20 was 20 nm. In the following Table 3, "SRO" means SrRuO3. In the following Table 3, "LNO" means LaNiO3. The piezoelectric thin film elements of Examples 19 and 20 were produced in the same manner as in Example 9, except that a second intermediate layer was formed.

[0098] The XRD patterns of the first electrode layers of Examples 19 and 20 were measured by the same method as in Example 1. In both Examples 19 and 20, the (002) plane of the Pt crystal constituting the first electrode layer was oriented in the normal direction to the surface of the first electrode layer, and the (200) plane of the Pt crystal was oriented in the in-plane direction of the surface of the first electrode layer.

[0099] The compositions of the piezoelectric thin films of Examples 19 and 20 were analyzed by the same method as in Example 1. In both Examples 19 and 20, the compositions of the piezoelectric thin films were consistent with the compositions of the targets. In other words, the compositions of the piezoelectric thin films of Examples 19 and 20 were the same as the composition of the piezoelectric thin film of Example 9.

[0100] In the same manner as in Example 1, the XRD patterns of the piezoelectric thin films of Examples 19 and 20 were measured. The XRD patterns of both Examples 19 and 20 showed that the piezoelectric thin films were composed of perovskite-type oxide crystals. In both Examples 19 and 20, at least a portion of the crystals contained in the piezoelectric thin film was tetragonal. In both Examples 19 and 20, the (001) plane of the crystal was preferentially oriented in the normal direction to the surface of the piezoelectric thin film.

[0101] The piezoelectric strain constant d of the piezoelectric thin films of Examples 19 and 20 was measured by the same method as in Example 1. 33,f was measured. 33,f is shown in Table 3 below.

[0102] [Table 3]

[0103] Example 21 In the process of producing the piezoelectric thin film element of Example 21, a first intermediate layer was not formed. In the process of producing the piezoelectric thin film element of Example 21, a first electrode layer made of crystalline SrRuO3 was formed directly on the entire surface of the crystalline substrate. The thickness of the first electrode layer of Example 21 was 200 nm. Except for these details, the piezoelectric thin film element of Example 21 was produced in the same manner as in Example 9.

[0104] The XRD pattern of the first electrode layer of Example 21 was measured by the same method as in Example 1. The lattice plane of the first electrode layer of Example 21 was not oriented in the in-plane direction of the surface of the first electrode layer. That is, in the case of Example 21, the crystal of the first electrode layer had no in-plane orientation.

[0105] The composition of the piezoelectric thin film of Example 21 was analyzed by the same method as in Example 1. The composition of the piezoelectric thin film of Example 21 was consistent with the composition of the target. In other words, the composition of the piezoelectric thin film of Example 21 was the same as the composition of the piezoelectric thin film of Example 9.

[0106] In the same manner as in Example 1, the XRD pattern of the piezoelectric thin film of Example 21 was measured. The XRD pattern of Example 21 also showed that the piezoelectric thin film was composed of perovskite-type oxide crystals. At least a part of the crystals contained in the piezoelectric thin film of Example 21 was tetragonal. In the case of Example 21 as well, the (001) plane of the perovskite crystal was preferentially oriented in the normal direction to the surface of the piezoelectric thin film.

[0107] The piezoelectric strain constant d of the piezoelectric thin film of Example 21 was measured by the same method as in Example 1. 33,f was measured. 33,f is shown in Table 4 below.

[0108] [Table 4]

[0109] (Examples 22 and 23) In preparing the target of Example 22, cobalt oxide was further used as a raw material in addition to gallium oxide. In the preparation of the target of Example 23, cobalt oxide was used as a raw material instead of gallium oxide. In other words, in the preparation of the target of Example 23, gallium oxide was not used. The composition of each of the targets in Examples 22 and 23 was represented by the following Chemical Formula 1B. In each of Examples 22 and 23, the values ​​of x, y, z, γ, and δ in the following Chemical Formula 1B were as shown in Table 5 below. x(Bi 0.5 K 0.5 )TiO3‐yBi(Ti 0.5 Mg 0.5 )O3‐zBi(Fe 1-γ (Ga 1-δ Co δ ) γ )O3(1B) The piezoelectric thin film elements of Examples 22 and 23 were fabricated in the same manner as in Example 1, except that the compositions of the targets used to form the piezoelectric thin film were different.

[0110] The XRD patterns of the first electrode layers of Examples 22 and 23 were measured by the same method as in Example 1. In both Examples 22 and 23, the (002) plane of the Pt crystal constituting the first electrode layer was oriented in the normal direction to the surface of the first electrode layer, and the (200) plane of the Pt crystal was oriented in the in-plane direction of the surface of the first electrode layer.

[0111] The composition of the piezoelectric thin film of each of Examples 22 and 23 was analyzed by the same method as in Example 1. In both cases of Examples 22 and 23, the composition of the piezoelectric thin film was consistent with the composition of the target. 1-δ Co δ Except for the above, the composition of the piezoelectric thin film in each of Examples 22 and 23 was the same as the composition of the piezoelectric thin film in Example 9.

[0112] In the same manner as in Example 1, the XRD patterns of the piezoelectric thin films of Examples 22 and 23 were measured. The XRD patterns of both Examples 22 and 23 showed that the piezoelectric thin films were composed of perovskite-type oxide crystals. In both Examples 22 and 23, at least a portion of the crystals contained in the piezoelectric thin film was tetragonal. In both Examples 22 and 23, the (001) plane of the crystal was preferentially oriented in the normal direction to the surface of the piezoelectric thin film.

[0113] The piezoelectric strain constant d of the piezoelectric thin films of Examples 22 and 23 was measured by the same method as in Example 1. 33,f was measured. 33,f is shown in Table 5 below.

[0114] [Table 5] [Industrial Applicability]

[0115] For example, the piezoelectric thin film element according to one aspect of the present invention may be applied to a piezoelectric transducer, a piezoelectric actuator, and a piezoelectric sensor. [Explanation of symbols]

[0116] 10...piezoelectric thin film element, 10a...piezoelectric transducer (ultrasonic transducer), 1...crystalline substrate, 2...first electrode layer, 3...piezoelectric thin film, 4...second electrode layer, 5...first intermediate layer, 6...second intermediate layer, D N ...normal direction to the surface of the first electrode layer, dn...normal direction to the surface of the piezoelectric thin film, uc...unit cell of the perovskite oxide crystal.

Claims

1. A piezoelectric thin film including a metal oxide having a perovskite structure, the metal oxide comprises bismuth, potassium, titanium, magnesium, iron, and an element M; The element M is at least one element selected from the group consisting of gallium and cobalt, At least a part of the metal oxide is at least one crystal selected from the group consisting of tetragonal and orthorhombic crystals, The (001) plane of the crystal is oriented in the normal direction to the surface of the piezoelectric thin film. Piezoelectric thin film.

2. The metal oxide is represented by the following chemical formula 1: In the following chemical formula 1, x, y, and z are each a positive real number, x+y+z is 1, In the following chemical formula 1, α is greater than 0 and less than 1, In the following chemical formula 1, β is greater than 0 and less than 1, In the following chemical formula 1, γ is 0.05 or more and 0.40 or less, In the following chemical formula 1, M is Ga 1-δ Co δ It is expressed as δ is greater than or equal to 0 and less than or equal to 1; The piezoelectric thin film according to claim 1 . x(Bi 1-α K α )4iッ 3 ‐yᄁii(エi 1-β ﷽ β )9 3 ‐zᄁi(ee 1-γ 7. γ )9 3 (1)

3. A three-dimensional coordinate system is composed of an X-axis, a Y-axis, and a Z-axis; Any coordinate in the coordinate system is represented as (X, Y, Z), The coordinates (x, y, z) in the coordinate system represent x, y, and z in Chemical Formula 1; Coordinate A in the coordinate system is (0.250, 0.005, 0.700), Coordinate B in the coordinate system is (0.450, 0.250, 0.300), The coordinate C in the coordinate system is (0.200, 0.500, 0.300), The coordinate D in the coordinate system is (0.005, 0.250, 0.700), The coordinates (x, y, z) are located within a quadrangle whose vertices are the coordinates A, B, C, and D. The piezoelectric thin film according to claim 2 .

4. It is an epitaxial film. The piezoelectric thin film according to claim 1 .

5. A ferroelectric thin film, The piezoelectric thin film according to claim 1 .

6. A piezoelectric thin film comprising the piezoelectric thin film according to claim 1. Piezoelectric thin film element.

7. A crystalline substrate; the piezoelectric thin film directly or indirectly overlapping the crystalline substrate; Equipped with 7. The piezoelectric thin film element according to claim 6.

8. A crystalline substrate; an electrode layer directly or indirectly overlying the crystalline substrate; the piezoelectric thin film directly or indirectly overlapping the electrode layer; Equipped with 7. The piezoelectric thin film element according to claim 6.

9. An electrode layer; the piezoelectric thin film directly or indirectly overlapping the electrode layer; Equipped with 7. The piezoelectric thin film element according to claim 6.

10. Further comprising at least one intermediate layer, the intermediate layer is disposed between the crystalline substrate and the electrode layer; 9. The piezoelectric thin film element according to claim 8.

11. Further comprising at least one intermediate layer, the intermediate layer is disposed between the electrode layer and the piezoelectric thin film; 9. The piezoelectric thin film element according to claim 8.

12. Further comprising at least one intermediate layer, the intermediate layer is disposed between the electrode layer and the piezoelectric thin film; 10. The piezoelectric thin film element according to claim 9.

13. the electrode layer includes platinum crystals; the (002) plane of the platinum crystal is oriented in a direction normal to the surface of the electrode layer; The (200) plane of the platinum crystal is oriented in the in-plane direction of the surface of the electrode layer.

9. The piezoelectric thin film element according to claim 8.

14. the electrode layer includes platinum crystals; the (002) plane of the platinum crystal is oriented in a direction normal to the surface of the electrode layer; The (200) plane of the platinum crystal is oriented in the in-plane direction of the surface of the electrode layer.

10. The piezoelectric thin film element according to claim 9.

15. A piezoelectric thin film according to any one of claims 1 to 5, Piezoelectric transducer.

16. A piezoelectric thin film element according to any one of claims 6 to 14, Piezoelectric transducer.